Improving performance of a trapezoidal-trough thermosyphon solar collector using peripherally wing-cut swirl generator. Issue 14 (14th November 2019) - Murugan, M.; Vijayan, R.; Saravanan, A.
ABSTRACT: In this present study, the performance of a newly modified solar collector named trapezoidal-trough solar collector (Tra-trough) has been examined using peripherally wing-cut swirl generator (PSG). The experiment has been executed at Government College of Engineering, Salem, Tamilnadu, India (Latitude: 11°66´N and Longitude: 78°15´E) with three different wing shapes including PSG with triangular wings (PSG-Tri), rectangular wings (PSG-Rec) and trapezoidal wings (PSG-Tra). The obtained results are contrasted with plain tube Tra-trough (TT-plain) solar collector under the same working condition. The experimental trials are made by keeping swirl ratio (Y = 3), wing-span ratio (b/W = 0.3) and wing-chord ratio (d/W = 0.4) as constant. The results obtained from the TT-plain are verified with the fundamental equations and found the deviations within ±11.21% for Nusselt number and ±8.24% for friction factor. From the experimental result, the PSG provides higher heat transfer rate over the TT-plain with/without typical swirl generator (TSG). The results also exposed that the PSG with trapezoidal wings (PSG-Tra) offers higher heat transfer rate and thermal efficiency than those given by other type of wing shapes. The thermal performance of trapezoidal wings (PSG-Tra) is enhanced up to 137% over the TT-plain. In addition, correlations for predicting the Nusselt number and friction factor have been developed. The deficiency of the predicted value for Nusselt number and friction factor are within ±10.31% and ±11.21%, respectively.